Sex-Related Differences of the Effect of Lipoproteins and Apolipoproteins on 10-Year Cardiovascular Disease Risk; Insights from the ATTICA Study (2002–2012) - Kouvari, Matina (Molecules, 2020)
The sex-specific effect of lipid-related biomarkers on 10-year first fatal/non fatal cardiovascular disease (CVD) incidence was evaluated. ATTICA study was conducted during 2001–2012. n = 1514 men and n = 1528 women (>18 years) from greater Athens area, Greece were recruited. Follow-up (2011–2012) was achieved in n = 2020 participants. Baseline lipid profile was measured. Overall CVD event was 15.5% (n = 317) (19.7% in men and 11.7% in women, p < 0.001). High density lipoprotein cholesterol (HDL-C) and triglycerides (TAG) were independently associated with CVD in women; per 10 mg/dL HDL-C increase, hazard ratio (HR) = 0.73, 95% confidence interval (95% CI) (0.53, 1.00); and per 10 mg/dL TAG increase, HR = 1.10, 95% CI (1.00, 1.21). Apolipoprotein A1 (ApoA1) (per 10 mg/dL increase, HR = 0.90, 95% CI (0.81, 0.99)) was inversely associated with CVD in women, while a positive association with apolipoprotein B100 (ApoB100) was observed only in men (per 10 mg/dL increase, HR = 1.10, 95% CI (1.00, 1.21)). Non-HDL-C was associated with CVD in the total sample (HR = 1.10, 95% CI (1.00, 1.21)) and in women (HR = 1.10, 95% CI (1.00, 1.21)); a steep increase in HR was observed for values >185 mg/dL in the total sample and in men, while in women, a raise in CVD risk was observed from lower values (>145 mg/dL). As for non-HDL-C/HDL-C and TC/HDL-C ratios, similar trends were observed. Beyond the common cholesterol-adjusted risk scores, reclassifying total CVD risk according to other lipid markers may contribute to early CVD prevention. Biomarkers such as HDL-C, non-HDL-C, and TAG should be more closely monitored in women.